9 Statutes at Large of the State of New York 188 (1875) - (:unkn) unknown (My University, 1874)
Ch. 721, § 3: No person shall at any time kill any wild duck, goose are or brant, with any device or instrument known as a swivel or punt gun, or with any gun other than such guns as are habitually raised at arms length and fired from the shoulder, or shall use any net, device or instrument, or gun other than such gun as aforesaid with intent to capture or kill any such wild duck, goose or brant under a penalty of one hundred dollars.
Keywords: HUNTING REGULATION